Study on Arsenic Contamination in Soil and Water in Five-selected Agro Ecological Zone (AEZ) of Bangladesh (The Agriculturists, 2010)
A research was carried out at the five different Agro-Ecological Zones (AEZ) of Bangladesh, viz. Tista Meander Floodplain (FP), High Ganges FP, Low Ganges FP, Active Ganges FP and Gopalganj-Khulna Bills during January 2001 to January 2002. The objectives were to assess the arsenic (As) concentration in the soil and water as well as to test tube well water samples and examines whether these exceed the acceptable limit of  As. Water of shallow tube wells (STW) and soil samples were collected from ten sites under five AEZs of Bangladesh. Considerable number of water samples showed high contents of arsenic, which ranged from 0.032 to 203.9 ?g/l. Out of 428 water samples, 155 were found unsafe (>10-50 ?g/l) for drinking purpose. However, out of 2648 soil samples collected from different Upazilas, only 4 samples collected from Chargat showed toxic level (>20 ?g/kg).